F42 Polymorphisms in the oxytocin receptor and their association with apathy and impaired social cognition in Huntington's disease. (12th September 2022) - Saiz-Rodríguez, Miriam; Gil-Polo, Cecilia; Diez-Fairen, Mónica; Martinez-Horta, Saul-Indra; Sampedro Santalo, Frederic; Collazo, Carla; Calvo, Sara; Alonso-García, Esther; Riñones-Mena, Esther; Aguado, Laura; Mariscal, Natividad; Muñoz-Siscart, Ignacio; et al.
Abstract : Background: Huntington's Disease (HD) is a neurodegenerative disorder characterized by cognitive, motor, and neuropsychiatric manifestations. Oxytocin is a neuropeptide studied for its role as a neuromodulator regulating multiple behaviors linked to social cognition. Genetic variation of oxytocin receptor (OXTR) might interact in the etiology and development of several impaired social behaviors. Our aim was to study OXTR polymorphisms and their relationship with apathy and social cognition in HD. Methods: OXTR was sequenced in 21 cases and 22 controls. We assessed apathy, anxiety, depression, and irritability [Hospital Anxiety and Depression Scale-Snaith Irritability scale, HADS-SIS], and social cognition [Ekman 60 faces test], motor symptoms and functionality with the Total functional capacity (TFC), and the Unified HD rating Scale (UHDRS). Results: We identified ten variants in OXTR. Three variants were classified as possibly damaging (p.Arg40Gly) or probably damaging (p.Leu46Pro, p.Thr102Asn). Subjects carrying the wild-type genotype of the synonymous variant p.Val45 showed a significantly lower score in the HADS-SIS scale, related to lower irritability (p=0.013). The only subject carrying the heterozygous genotype of the synonymous variant p.Leu62 showed a significantly higher score on Ekman scale, compared to wild-type (p=0.049), however, this finding was not confirmed after bootstrapping. Conclusion: Variations in OXTR could have a relevant role in the correct development of social and cognitive functions. Future approaches will include the molecular study of p.Arg40Gly, p.Leu46Pro and p.Thr102Asn to confirm their pathogenicity, as well as the validation of the influence of p.Val45 and p.Leu62 variants for their involvement in irritability and social cognition in HD.